N-Type Conductivity in Wurtzite Mn-Doped GaN thin Films Grown by Plasma Assisted MOCVD - Budi Mulyanti; Agus Subagio; Edi Supriyanto; Heri Sutanto; Fitri Suryani Arsyad; Pepen Arifin; Maman Budiman; Mohamad Barmawi (Jurnal Matematika & Sains, 2006)
Ferromagnetic semiconductor GaN:Mn thin films were successfully grown by plasma-assisted metalorganic chemical vapor deposition (PA-MOCVD) method on c-plane sapphire substrate. The films were grown at various Mn source flux in the range of 5 - 40 sccm and growth temperature which was lower than that of MOCVD themal, i.e. in the range of 625-700 Â°C. Cyclopentadienyl manganese tricarbonyl (CpMnT) was used as a source of Mn. X-ray diffraction patterns confirmed that GaN:Mn films are wurtzite and do not show second phase for film with Mn concentration up to 6.4% at 650 Â°C of growth temperature. Hall effect measurements show n-type characteristics. The carrier (electron) density tends to decreases and Hall mobility tends to with the increase of Mn concentration is increased. Hysteresis curves observed from VSM measurements indicated that all of the samples are ferromagnetic at room temperature.